Progress of Photocapacitors - Flores-Diaz, Natalie; De Rossi, Francesca; Das, Aparajita; Deepa, Melepurath; Brunetti, Francesca; Freitag, Marina (Chemical reviews, 2023)
In response to the current trend of miniaturization of electronic devices and sensors, the complementary coupling of high-efficiency energy conversion and low-loss energy storage technologies has given rise to the development of photocapacitors (PCs), which combine energy conversion and storage in a single device. Photovoltaic systems integrated with supercapacitors offer unique light conversion and storage capabilities, resulting in improved overall efficiency over the past decade. Consequently, researchers have explored a wide range of device combinations, materials, and characterization techniques. This review provides a comprehensive overview of photocapacitors, including their configurations, operating mechanisms, manufacturing techniques, and materials, with a focus on emerging applications in small wireless devices, Internet of Things (IoT), and Internet of Everything (IoE). Furthermore, we highlight the importance of cutting-edge materials such as metal-organic frameworks (MOFs) and organic materials for supercapacitors, as well as novel materials in photovoltaics, in advancing PCs for a carbon-free, sustainable society. We also evaluate the potential development, prospects, and application scenarios of this emerging area of research.